In The Shadows of Governance: Exploring the Untamed Territories of Administrative Discretion - Aris Sarjito (Program Studi Administrasi Negara Universitas Serang Raya, 2023)
This research explores administrative discretion's potential in unexplored territories within governance structures, highlighting its impact on public policy and organizational functioning. The primary aim of this study is to comprehensively understand and map these untamed territories, offering insights into their identification and implications for governance effectiveness. Qualitative research methods are employed, thoroughly analyzing secondary data sources, including academic literature, government reports, and case studies. Through this method, the study explores the multifaceted dimensions of administrative discretion, identifies the uncharted territories where it operates, and assesses its implications on the overall effectiveness of governance structures. Research findings are: Legal, political, and organizational factors all impact the multifaceted concept of administrative discretion in public administration. This concept is crucial for effective and accountable governance, using theoretical frameworks like principal-agent theory. Identifying and mapping untamed territories in governance involves a multi-faceted approach, requiring document analysis, stakeholder consultations, and expert interviews to develop responsive governance structures. Assessing the impact of untamed territories on governance effectiveness is crucial for responsiveness to evolving challenges. Traditional models need a paradigm shift, embracing innovation, collaboration, and adaptability to navigate complexities